Forestiera veracruzana (Oleaceae), a new species from the riparian forests of central Veracruz, Mexico - Palacios-Wassenaar, Olivia M.; Castillo-Campos, Gonzalo (Phytotaxa, 2021)
The new species Forestiera veracruzana is described and illustrated. This newly described plant is part of the tree and shrub strata of riparian forests in the lowlands and hills of the Mexican states of Veracruz and Tabasco. Forestiera veracruzana is morphologically similar to F. corollata, and F. isabeliae by the presence of petals, and possibly to F. rhamnifolia, which also grow in similar environments, but it can be readily distinguished from these by its polygamodioecious condition, the length of peduncle, and the length and shape of pistil at anthesis.